Viability and reconstitution of delta-endotoxins from Bacillus thuringiensis var. israelensis extracts after forty years of storage against Aedes aegypti (Diptera: Culicidae) - Fernández Chapa, David Daniel; Luna Olvera, Hugo Alberto; Ramírez Villalobos, Jesica María; Rojas Verde, María Guadalupe; Arévalo Niño, Katiushka; Galán Wong, Luis Jesús (Springer, 2021)
Background: Bacillus thuringiensis subsp. israelensis (Bti) produces insecticidal endotoxins known as Cry and Cyt. Its efficiency and specificity make it the most widely used substance as a biopesticide for controlling disease from vector insects, such as mosquitoes, responsible for important human diseases such as malaria, filariasis, dengue, and yellow fevers. To date, it is proven difficult to develop a commercial product that has more than 2 years of shelf life, and there is little information on the viability of these commercial proteins under prolonged storage conditions. Results: This study aimed to evaluate biological activity of reconstituted Bti endotoxins after 40 years of storage against the mosquito Aedes aegypti larvae. Five concentrations of Bti extracts were used for bioassays against 3rd and 4th instars of A. aegypti larvae. All reconstituted endotoxins from stored extracts showed a potency increase. The strain HD-500 from extract 3260 was the most effective insecticide (LC50 = 0.0014 mg/l), followed by 3756 (LC50 = 0.0037 mg/ l). These strains were particularly notable, increasing their larvicidal potency one hundredfold and one thousandfold, respectively. Protein profiles in polyacrylamide gels revealed a greater presence of Cyt toxins compared to the stored Bti extracts, which maintained their activity at high concentrations. Conclusion: The reconstituted Bti strains presented a great biological activity against A. aegypti larvae, specially extract 3260 (median lethal concentration (LC50) value = 0.0014 mg/l). This considerable larvicidal activity after 40 years under storage was an encouraging signal for the development of future formulation strategies regarding their useful life. The stability of extracts of stored endotoxins produced by Bti decreased significantly, particularly Cyt1A protein, which is responsible for their synergistic activity